1991
DOI: 10.2351/1.4745287
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Oxidation in Laser Cutting Stainless and Mild Steel

Abstract: This paper gives the results of a detailed examination of the particles ejected from the cut zone during CO2 laser cutting of mild and stainless steels. Cuts were carried out over a range of material thickness at the optimum speed for each at a laser power of 900 Watts. Particles ejected from the cut zone were collected and analyzed to establish their chemical and physical characteristics. Analysis techniques included Scanning Electron Microscopy, wet chemical analysis, optical microscopy, metallography and pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 0 publications
1
22
0
Order By: Relevance
“…It was also observed that reduction in the minimum required spot overlapping to achieve higher cutting speed is difficult when argon is used as assist gas in place of oxygen. This is due to the fact that during stainless steel cutting with oxygen as assist gas, a large amount of energy is generated by the exothermic reaction [40]. This also supports the fact that exothermic reaction is one of the important factors for reduction in minimum required spot overlapping during stainless steel cutting and this value of reduced spot overlapping enhances the cutting speed of stainless steel for the same amount of laser pulse energy.…”
Section: Results and Analysismentioning
confidence: 76%
“…It was also observed that reduction in the minimum required spot overlapping to achieve higher cutting speed is difficult when argon is used as assist gas in place of oxygen. This is due to the fact that during stainless steel cutting with oxygen as assist gas, a large amount of energy is generated by the exothermic reaction [40]. This also supports the fact that exothermic reaction is one of the important factors for reduction in minimum required spot overlapping during stainless steel cutting and this value of reduced spot overlapping enhances the cutting speed of stainless steel for the same amount of laser pulse energy.…”
Section: Results and Analysismentioning
confidence: 76%
“…This small difference between the use of reactive and inert gases shown in the hole entrance diameter, can be produced by an exothermic reaction between oxygen and some iron suboxides that are present in the slate. This reaction contributes with an additional amount of energy in the interaction zone between the laser and the slate [9].…”
Section: Resultsmentioning
confidence: 98%
“…An alternative to increase the assist gas performance is the utilization of off-axial supersonic nozzles. This technique has been successfully used for cutting metals such as stainless and mild steel [24] or 2024-T3 aluminium alloy [18]; ceramics such as tiles [25] or mullite-alumina [26]; polymers such as polyethylene, polypropylene, polycarbonate [27] or polymethyl methacrylate [28], or wood [29]; however, it has not been widely explored for cutting granite stones.…”
Section: Introductionmentioning
confidence: 99%